Effects of ropivacaine, bupivacaine and sufentanil in colon and pancreatic cancer cells in vitro. (May 2015) - Bundscherer, A.; Malsy, M.; Gebhardt, K.; Metterlein, T.; Plank, C.; Wiese, C.H.; Gruber, M.; Graf, B.M.
Graphical abstract: Abstract: The perioperative period is supposed to be a vulnerable period for cancer progression. Results of clinical studies indicate that the use of regional anesthesia can influence and improve oncological outcome of cancer patients. Uncontrolled cell proliferation and resistance to apoptotic cell death are important characteristics of solid tumors. The aim of this study was to investigate the effects of the clinically used local anesthetics ropivacaine or bupivacaine and the opioid analgesic sufentanil on cell proliferation, cell cycle distribution and apoptosis of colon (HT 29 and SW 480) and pancreatic (PaTu 8988t and PANC 1) cancer cell lines in vitro . Cell proliferation was measured by Cell Proliferation ELISA BrdU Assay. Apoptosis was analyzed by annexin V staining and cell cycle distribution was detected by flow cytometry. Ropivacaine, bupivacaine and sufentanil did not change apoptosis rate and cell cycle distribution in clinically concentration. Only high concentrations of ropivacaine or bupivacaine revealed antiproliferative potency. Protective effects of epidural anesthesia observed in clinical studies seem not to be based on direct effects of these drugs on cancer cells.